Citizen Science in Science-Physics Class: Building Contextual Climate Change Literacy - Andini, Elvina Risma; Siswanto, Joko (Lontar Physics Today, 2025)
This study aims to examine the potential of integrating Citizen Science (CS) into science-physics learning as a pedagogical approach that can help shape a contextual understanding of climate change. This study used the Systematic Literature Review (SLR) method with reference to the PRISMA 2020 guidelines. The review process was carried out through several steps, namely problem identification, literature search in various databases, determination of inclusion and exclusion criteria, selection of articles, and thematic analysis of literature that met the criteria. Of the 35 articles identified, 15 were selected for further in-depth analysis. The literature review indicates that the integration of CS into science-physics learning can effectively improve cognitive aspects (scientific literacy, critical thinking skills, and creativity), affective (positive attitudes towards the environment, self-confidence, and relationships with the scientific community), and behavioral (awareness of pro-environmental actions). However, significant behavioral changes are still limited, and implementation faces obstacles such as limited time, lack of teacher competence, and integration with the official curriculum. The uniqueness of this study lies in mapping the contribution of Citizen Science in strengthening students' climate literacy comprehensively. Citizen Science serves not only as a science learning method but also as a medium of scientific and social participation that connects scientific knowledge, environmental awareness, and concrete action.